"Towards West African coastal social-ecosystems sustainability: Interdisciplinary approaches". (1st October 2021) - Dada, Olusegun; Almar, Rafael; Morand, Pierre; Menard, Frederic
Abstract: The coastal system can be regarded as co-evolving socio-economic and ecological systems undergoing intense environmental pressures owing to the mechanisms of change exerted by human activities against a background of natural change. Understanding and managing ecological responses to these changes in the coastal areas require interdisciplinary approaches. Here, we develop a new approach of coastal socio-ecological systems (CSES) based on earlier work on the press-pulse dynamics (PPD) socio-ecological systems. To show the relevance of the modified (mPPD) framework, we applied it to two unique features (mangroves and beach systems) of the western African coastal (WAC) systems. Then, we constructed plausible 21st-century coastal systems scenarios at the coast based on a set of descriptive indicators (population growth, economic development, environmental quality, governance, technological advancement and climate change) for a better understanding and sustainable management planning of WAC systems. We found that different indicators characterizing each scenario will exert different pressures on the WAC systems, under the forms of the long-term press and short-term pulse events. The cross-cutting narratives of the different future scenarios in the face of climate change using the mPPD framework offer valuable insight into the development of WAC management strategies, policies and other agendas. It helps to define the plausible implications of following, or not, a particular management path. The inconsistencies between the aspirations of different resource users and lack of coordination of human activities taking place on land and in the coastal zone, partly due to fragmentation of institutions and weak coastal governance are revealed. In this context, the mPPD-CSES framework can be used to investigate how ecosystems can experience different (intensities of) press as well as different frequencies of the pulse. Thus, its adaptability to construct future coastal vulnerability scenarios adds to its usefulness as a robust and dependable integrated coastal zone management tool. Graphical abstract: Image 1 Highlights: We modified the press-pulse dynamics (mPPD) social-ecological systems (SES) framework to develop coastal SES (CSES). We applied mPPD-CSES to two unique features (mangroves and beaches systems) of the West African coastal (WAC) systems. Then, we constructed plausible 21st-century scenarios for WAC systems using mPPD- CSES. We found that different indicators characterizing each scenario will exert different pressures on the WAC systems. mPPD- CSES helps to define the plausible implications of following, or not, a particular management path.